OPTIMIZATION OF PROCESS PARAMETERS FOR IMPROVED PRODUCTION OF ANTIMICROBIAL METABOLITES FROM NOCARDIOPSIS FLAVESCENS VJMS-18 ISOLATED FROM SOUTH-COASTAL REGIONS OF ANDHRA PRADESH, INDIA - MOGILI, MARY SWAPNA; MUVVA VIJAYALAKSHMI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of the present study is to optimize the cultural parameters for Nocardiopsis flavescens VJMS-18 strain isolated from marine sediment samples of the south-coast of Andhra Pradesh, India. Methods: The strain N. flavescensVJMS-18 was identified based on morphological, physiological, biochemical and molecular approaches. The effect of environmental parameters such as incubation period, pH, temperature and salt concentration and the effect of various nutrients such as carbon and nitrogen sources and minerals on the bioactive metabolite production by N. flavescens VJMS-18 was evaluated by employing agar well diffusion assay. Results: The nutritional requirements and cultural conditions to enhance the yield of secondary metabolites are optimized under shake flask conditions. ISP-2 medium supplemented with sodium chloride at 3% maintained at pH 7.0 supported the maximum yield of secondary metabolites by the strain when incubated at 35°C for 8 days. The strain exhibited a broad spectrum of antagonistic activity against Gram-positive (Staphylococcus aureus and Bacillus megaterium) and Gram-negative bacteria (Klebsiella pneumoniae, Escherichia coli and Pseudomonas aeruginosa) as well as fungus (Candida albicans). Conclusion: It was found that the antimicrobial metabolite production by the strain was positively influenced by carbohydrates, nitrogen sources and minerals.